Diversity of reductive dehalogenase genes from environmental samples and enrichment cultures identified with degenerate primer PCR screens - Hug, Laura A.; Edwards, Elizabeth A. (Frontiers in Microbiology, 2013)
Reductive dehalogenases are the critical enzymes for anaerobic organohalide respiration, a microbial metabolic process that has been harnessed for bioremediation efforts to resolve chlorinated solvent contamination in groundwater and is implicated in the global halogen cycle. Reductive dehalogenase sequence diversity is informative for the dechlorination potential of the site or enrichment culture. A suite of degenerate PCR primers targeting a comprehensive curated set of reductive dehalogenase genes was designed and applied to twelve DNA samples extracted from contaminated and pristine sites, as well as six enrichment cultures capable of reducing chlorinated compounds to non-toxic end-products. The amplified gene products from four environmental sites and two enrichment cultures were sequenced using Illumina HiSeq, and the reductive dehalogenase complement of each sample determined. The results indicate that the diversity of the reductive dehalogenase gene family is much deeper than is currently accounted for: one-third of the translated proteins have less than 70% pairwise amino acid identity to database sequences. Approximately 60% of the sequenced reductive dehalogenase genes were broadly distributed, being identified in four or more samples, and often in previously sequenced genomes as well. In contrast, 17% of the sequenced reductive dehalogenases were unique, present in only a single sample and bearing less than 90% pairwise amino acid identity to any previously identified proteins. Many of the broadly distributed reductive dehalogenases are uncharacterized in terms of their substrate specificity, making these intriguing targets for further biochemical experimentation. Finally, comparison of samples from a contaminated site and an enrichment culture derived from the same site eight years prior allowed examination of the effect of the enrichment process.